MANAJEMEN SEKOLAH DALAM MENGEMBANGKAN ASPEK SOSIAL EMOSIONAL ANAK USIA DINI DI PAUD DESA KEMBANG AYUN KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Diya; Mus Mulyadi; Fidhia Andani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social-emotional development is one of the essential aspects that should be fostered during early childhood, as it influences children's ability to interact, regulate emotions, cooperate, and adapt to their social environment. The success of developing this aspect is closely related to effective school management, which includes planning, organizing, implementation, and evaluation of educational programs. This study aimed to describe school management practices in developing the social-emotional aspects of early childhood education at PAUD Desa Kembang Ayun, Pondok Kelapa District, Central Bengkulu Regency. This research employed a qualitative approach with a descriptive research design. The participants consisted of the principal and teachers who were directly involved in planning and implementing learning activities. Data were collected through observations, in-depth interviews, and documentation, and were analyzed using data condensation, data display, and conclusion drawing based on the interactive model of Miles, Huberman, and Saldaña. The validity of the data was ensured through source and technique triangulation. The findings revealed that school management was implemented through four main managerial functions. Planning was conducted by integrating social-emotional development into daily learning programs. Organizing involved the distribution of responsibilities among teachers and the establishment of effective coordination. Implementation was carried out through play-based learning activities, habituation programs, collaborative learning, and positive social interactions that supported children's social-emotional growth. Evaluation was conducted continuously through systematic observation of children's development to improve the quality of learning programs. Supporting factors included teachers' commitment and strong collaboration between the school and parents, while limited educational facilities and insufficient professional development opportunities for teachers were identified as the main challenges. The study concludes that school management at PAUD Desa Kembang Ayun has played a significant role in fostering children's social-emotional development. However, strengthening teachers' professional competence and improving educational facilities are necessary to optimize the implementation of school management in early childhood education.